2016
DOI: 10.1002/ejoc.201501552
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3‐Disubstituted Quinazolinone Derivatives through Copper Catalyzed C–H Amidation Reactions

Abstract: The synthesis of quinazolinone derivatives was achieved from 2‐iodobenzamide derivatives and various benzylamines, allylamine, and cinnamylamine derivatives through a one‐pot copper‐catalyzed reaction. In this reaction, the amine component (benzylamine/allylamine/cinnamylamine) is N‐arylated with 2‐iodobenzamide derivatives through Ullman coupling, followed by an intramolecular C–H amidation in the presence of copper catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 67 publications
0
17
1
Order By: Relevance
“…The results collected in Table 1 showed that the reaction performed under 100 °C using Cs 2 CO 3 as a base provided the highest yield (Entries 1–8, Table 1 ). The further screening of the catalyst (Entries 9–15, Table 1 ) showed that copper (Cu (II)) salts gave higher yields of product 4aa (Entries 12 and 14, Table 1 ) than Cu (I) in this case, being totally different from the reported results [ 11 , 12 , 25 , 29 , 31 ].…”
Section: Discussion and Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…The results collected in Table 1 showed that the reaction performed under 100 °C using Cs 2 CO 3 as a base provided the highest yield (Entries 1–8, Table 1 ). The further screening of the catalyst (Entries 9–15, Table 1 ) showed that copper (Cu (II)) salts gave higher yields of product 4aa (Entries 12 and 14, Table 1 ) than Cu (I) in this case, being totally different from the reported results [ 11 , 12 , 25 , 29 , 31 ].…”
Section: Discussion and Resultscontrasting
confidence: 86%
“…A variety of convenient methodologies have been developed for the synthesis of quinazolinones [ 10 , 11 , 12 , 13 ]. o -Aminobenzamides [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and o -bromobenzamides [ 12 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] are the most frequently used starting materials by far, and o -Aminobenzoic acid [ 32 ], o -haloaniline [ 26 , 33 ], and isatoic anhydride [ 34 ] were also introduced. Alternatively, o -aminobenzonitrile [ 35 , 36 , 37 ] was applied to prepare quinazolinones by Wu and co-workers [ 35 ], considering that the variation of o -aminobenzonitriles is much more available than o -aminobenzamides.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods generally suffer from drawbacks such as complex homogeneous catalytic systems or expensive feedstocks. Recent examples of oxidative condensation reactions of alcohols, methyl arenes, and amines often require excess amounts of oxidants (Scheme a, route 2). Wu et al.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, homogeneous copper catalysts have been used successfully for a variety of organic reactions. 3645 Furthermore, the catalyst systems need to be developed further because of the possibility of metal contamination in the final product, lack of recyclability of the metal catalyst, use of additives, and expensive ligand system. Copper oxide (CuO) nanoparticles (NPs) can be applied in catalysis, gas sensing, and photocatalysis.…”
Section: Introductionmentioning
confidence: 99%